Geospatial AI for Environmental Health: Understanding the Impact of the Environment on Public Health in Jammu and Kashmir - Kumar, Ravi; Verma, Shivam; Kaushik, RajKumar (International Journal of Psychosocial Rehabilitation, 2019)
In this study work, the complicated link between the environment and public health in Jammu and Kashmir is looked at. The region’s varied scenery, with mountains and fields, and its unpredictable weather have a big effect on people’s health and happiness. The study aims to make the complicated links between these factors and their health affects еasiеr to understand by using methods that are easy to get to, like satellite images, data on air and water quality, and social factors. It is talked about in easy words what the study means for improving the health of people in Jammu and Kashmir.